Profitable Urban Public Spaces Significant Role in Building Safer and More Sustainable Societies: Cairo as a Promising Case - Morsy, Ahmed Abd Elghany (Majallat al-ʻimārah wa-al-funūn wa-al-ʻulūm al-insānīyah, 2022)
The swift growth of towns and cities can lead to an evident retrogradation, for instance, the current state's efforts to develop open spaces. Urban open spaces in Egypt in general, and in Cairo in particular need innovative ideas. Hence, an insistent need for the development and creation of productive and profitable urban open spaces is highly required. Cairo city faces many obstacles such as the rapid increase in urban population which leads to a rapid aborting urban expansion of the city. Accordingly, public urban spaces tend to reflect the comprehensive power of the merge between the urban and the economic activities of a 'productive sustainable city'. The city`s design is considered as a response to the challenges of building a pro-active and resilient future for contemporary cities. Moreover, these challenges were based on a vision of an urban future of physical, social, and systemic introduction of what we call 'Continuous Productive Urban space. Thus, building a new maintained urban infrastructure and assisting a re-definition of open urban space usages were both addressed aspects: the establishment of an urban sustainable site and the creation of a productive, and profitable public space. After many years of the absence of profitable activities from urban design agendas, it is now recognized as an important subject that can shape both spaces, and cities as well as the everyday life and local identity of its inhabitants. The challenge resides in reinvent proactive proximities, close circular economies, new alternatives of co-production and eco-sharing within a resilient, sustainable, participatory and localized urban space production at the heart of the metropolis. The goal is a more sustainable city. Therefore, the study aims at exploring the profitability and the productivity of the city's public urban spaces' design, besides, the creation of unprecedented opportunities for more sustainable and social interactions within the urbanity. The paper will also trace some examples of profitable sustainable urban space's remarkable shift from a marginal interest to one at the center of contemporary urban discourse locally and internationally. Furthermore, It suggests a solid strategy for the introduction of connecting productive activities with cities.